House rules : a novel - Picoult, Jodi, 1966- (New York : Atria Books, 2010)
A teenager with Asperger's syndrome-- smart, quirky, with a passion for crime scene analysis--winds up on trial for murder.
Keywords: Asperger's syndrome -- Fiction; Autistic youth -- Fiction; Forensic sciences -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction